Urban-rural relations : a geographical analysis - Ravinder Kaur, 1970- (New Delhi : Anmol Publications, 1995)
With special reference to India.
Includes bibliographical references (p. 133-139).
Keywords: Rural-urban migration -- India; Commuting -- India; Rural-urban relations -- India